The Biosecurity Individual A Cultural Critique of the Intersection between Health, Security, and Identity - Offizier, Frederike (American Culture Studies, 2023)
Discoveries in biomedicine and biotechnology, especially in diagnostics, have made prevention and (self)surveillance increasingly important in the context of health practices. Frederike Offizier offers a cultural critique of the intersection between health, security and identity, and explores how the focus on risk and security changes our understanding of health and transforms our relationship to our bodies. Analyzing a wide variety of texts, from life writing to fiction, she offers a critical intervention on how this shift in the medical gaze produces new paradigms of difference and new biomedically facilitated identities: biosecurity individuals.